1006. ANTHORRHIZA ECHINELLA: An ant‐plant of the Rubiaceae. (9th November 2021) - Campbell, Laura C. E.; Huxley, Camilla R.; Jebb, Matthew; Thorogood, Chris J.; Chomicki, Guillaume
Summary: The rare ant‐plant Anthorrhiza echinella C.R.Huxley & Jebb from Papua New Guinea is described and illustrated. The outlook of the species and the importance of ex situ conservation strategies for this and other ant‐plants are discussed in the context of botanic garden collections. Based on the plant's likely current distribution, we have assessed the species under the IUCN Red List as Endangered (EN) under criteria B1ab(iii) + 2ab(iii).